A suicide symphony - Deng, Kaile (2008)
This report aims to chart the process of making A Suicide Symphony from conceptualization, to the final completion of a 23-minute short video. The report also documents the challenges faced and the lessons learned in the year-long process. A Suicide Symphony is a product of the combined effort of QUiETUS Films, comprising Deng Kaile (Director, Co-Writer), Kang De Long, Christopher (Director of Photography, Sound Designer), Tan Xue Yan (Writer, Art Director, Editor) and Lu Xinyi (Producer, Casting Director, Location Manager).